PENGARUH PENGUNAAN METODE “RULE OF THUMB PRICING” UNTUK MEMAKSIMUMKAN LABA PETERNAK AYAM BROILER DI KECAMATAN TUMPANG KABUPATEN MALANG - Dullah, Mohammad - (Magister Manajemen Universitas Wisnuwardhana, 2017)
The increase in the real business sector in the field of broiler farms in this poor district of the statistics is very good, but will be inversely if studied in depth about the output (profit) generated by the breeders. Return on investment (ROI) on this business is relatively small, dependence on feed from factories, dependence of seeds, investment of making the cage is not small, not to mention the Human Resources and Management of breeders is low so it needs to be studied in depth so that the farmers this is not a loss. Because of the many problems that must be solved by the breeders, this study limits and focuses on efforts to increase broiler farmers profit in Tumpang District, Malang Regency. This research is titled